Principle of Responsibilities and Sanctions in Pollutions of the Marine Environment by Offshore Minning - Sunyowati, Dina (Indonesian Journal of International Law, 2011)
In a period of 5 (five) years of pollution of the marine environment caused by exploration and exploitation on the continental shelf and the area (the seabed) is increasing. Like the marine pollution in the Timor Sea which transnational pollution, because it involves three countries, namely Australia, Timor Leste, and Indonesia. Settlement efforts to revolve the impact caused by too have done well by the Australian Government nor by the Indonesian Government. Pollution of the marine environment also occurs in blasting offshore mining that pollute the Gulf of Mexico. As mentioned in the 1982 UNCLOS, Article 208 that one of the sources of marine pollution is from the exploration and exploitation under the jurisdiction of a country. For that, if there is contamination and pollution, then the polluter is responsible and obliged to recovery the environment as soon as possible, so that ecosystems and the biota in the ocean can be saved. In addition to several conventions in 1982 UNCLOS also provides for compensation and the responsibility for restoring environmental pollutants, such as the Stockholm Declaration of 1972, Agenda 21 Global and Offshore Pollution Liability Agreement, 1975. The principle used to sue the polluter polluter pays principle, liability based on fault principle, and the precautionary principle. In a period of 5 (five) years of pollution of the marine environment caused by exploration and exploitation on the continental shelf and the area (the seabed) is increasing. Like the marine pollution in the Timor Sea which transnational pollution, because it involves three countries, namely Australia, Timor Leste, and Indonesia. Settlement efforts to revolve the impact caused by too have done well by the Australian Government nor by the Indonesian Government. Pollution of the marine environment also occurs in blasting offshore mining that pollute the Gulf of Mexico. As mentioned in the 1982 UNCLOS, Article 208 that one of the sources of marine pollution is from the exploration and exploitation under the jurisdiction of a country. For that, if there is contamination and pollution, then the polluter is responsible and obliged to recovery the environment as soon as possible, so that ecosystems and the biota in the ocean can be saved. In addition to several conventions in 1982 UNCLOS also provides for compensation and the responsibility for restoring environmental pollutants, such as the Stockholm Declaration of 1972, Agenda 21 Global and Offshore Pollution Liability Agreement, 1975. The principle used to sue the polluter polluter pays principle, liability based on fault principle, and the precautionary principle. In a period of 5 (five) years of pollution of the marine environment caused by exploration and exploitation on the continental shelf and the area (the seabed) is increasing. Like the marine pollution in the Timor Sea which transnational pollution, because it involves three countries, namely Australia, Timor Leste, and Indonesia. Settlement efforts to revolve the impact caused by too have done well by the Australian Government nor by the Indonesian Government. Pollution of the marine environment also occurs in blasting offshore mining that pollute the Gulf of Mexico. As mentioned in the 1982 UNCLOS, Article 208 that one of the sources of marine pollution is from the exploration and exploitation under the jurisdiction of a country. For that, if there is contamination and pollution, then the polluter is responsible and obliged to recovery the environment as soon as possible, so that ecosystems and the biota in the ocean can be saved. In addition to several conventions in 1982 UNCLOS also provides for compensation and the responsibility for restoring environmental pollutants, such as the Stockholm Declaration of 1972, Agenda 21 Global and Offshore Pollution Liability Agreement, 1975. The principle used to sue the polluter polluter pays principle, liability based on fault principle, and the precautionary principle.